New estimates of the burden of acute community‐acquired infections among older people with diabetes mellitus: a retrospective cohort study using linked electronic health records. Issue 5 (12th February 2014) - McDonald, H. I.; Nitsch, D.; Millett, E. R. C.; Sinclair, A.; Thomas, S. L.
Abstract Aim To describe the incidence of acute community‐acquired infections (lower respiratory tract infections, urinary tract infections and sepsis) among the UK population aged ≥65 years with diabetes mellitus, and all‐cause 28‐day hospital admission rates and mortality. Methods We used electronic primary care records from the Clinical Practice Research Datalink, linked to death certificates and Hospital Episode Statistics admission data, to conduct a retrospective cohort study from 1997 to 2011. Results Among the 218 805 older people with diabetes there was a high burden of community‐acquired infection, lower respiratory tract infections having the highest incidence (crude rate: 152.7/1000 person‐years) followed by urinary tract infections (crude rates 51.4 and 147.9/1000 person‐years for men and women, respectively). The incidence of all infections increased over time, which appeared to be driven by the population's changing age structure. Most patients diagnosed with pneumonia and sepsis were hospitalized on the same day (77.8 and 75.1%, respectively). For lower respiratory tract infections and urinary tract infections, a large proportion of 28‐day hospitalizations were after the day of diagnosis (39.1 and 44.3%, respectively), and a notable proportion of patients (7.1 and 5.1%, respectively) were admitted for a cardiovascular condition. In the 4 weeks after onset, all‐cause mortality was 32.1% for pneumonia (3115/9697), 31.7% for sepsis (780/2461), 4.1% for lower respiratory tract infections (5685/139 301) and 1.6% for urinary tract infections (1472/91 574). Conclusions The present large cohort study provides up‐to‐date detailed infection incidence estimates among older people with diabetes in the community, with variation by age, sex and region and over time. This should be of use for patient communication of risk and future healthcare planning.